Предмет: Математика,
автор: Аноним
* (-6)²+(1/3)²÷0,1¹
* -5×(-2)⁴+(-3)³+7×4⁰
* (1/3-1/6)²×(-36)+1/4×4⁰
Ответы
Автор ответа:
0
-5х(-2)^4+(-3)^3+7х4^0=-5х16+(-27)+7х1=-80-27+7=-100
(1/3-1/6)^2х(-36)+1/4х4^0=(1/6)^2х(-36)+1/4х1=(1/36)х(-36)+1/4=(-1)+1/4=(-3/4)
(-6)^2+(1/3)^2/0,1^1=36+(1/9:1/10)=36+(1/9х10/1)=36+10/9=324/9+10/9=334/9
(1/3-1/6)^2х(-36)+1/4х4^0=(1/6)^2х(-36)+1/4х1=(1/36)х(-36)+1/4=(-1)+1/4=(-3/4)
(-6)^2+(1/3)^2/0,1^1=36+(1/9:1/10)=36+(1/9х10/1)=36+10/9=324/9+10/9=334/9
Похожие вопросы
Предмет: Английский язык,
автор: miafazyl
Предмет: Информатика,
автор: kykareeky
Предмет: География,
автор: muhsino4ka
Предмет: История,
автор: spb1234
Предмет: Алгебра,
автор: Xshamil